IMPLEMENTASI PERANGAKAT KERAS SISTEM MONITORING INTERNET OF THINGS (IOT) PADA PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO - Hasvienda M Ridlwan (Power Elektronik : Jurnal Orang Elektro, 2022)
This paper will discuss the hardware design of a remote monitoring system in a micro-hydro power plant. The existence of damage to the PLTMH due to fluctuating voltage causes disruption of electricity supply to consumers in the form of blackouts, but this is not known by the electricity provider at the location of the PLTMH and the load is quite difficult to achieve and there are direct work priorities that do not allow it to be carried out at any time. The delay in information on the condition of the MHP is an obstacle in making improvements and making the MHP system more reliable. In this PLTMH a system is designed that can monitor the performance of the MHP. The design of this remote monitoring system can unify the current, voltage, and output power of the load generator by using the Robotdyn Uno+wifi microcontroller and 16-bit ADC, as well as designing a low-voltage notification system on the PLTMH repair so that the indication of low voltage can be done in real time via Internet of Things (IoT)-based wireless communication (Wi-Fi) carried out with interface displays in the form of Blynk and Telegram applications. The result of this design is that the reading error in this design is 0.24 – 0.4% on reading the voltage, 0 – 2% on reading the current by calibrating the FLUKE 179 and 375 multimeters and has succeeded in sending data in real time.